A boric acid-assisted hydrothermal process for preparation of mesoporous silica nanoparticles with ultra-large mesopores and tunable particle sizes. Issue 12 (15th June 2023) - Sun, Rui; Zhou, Jiugong; Wang, Wei
Abstract: This work reports that monodispersed ultra-large mesopore mesoporous silica nanoparticles (LP-MSNs) can be facilely prepared by a simple and highly effective boric-assisted hydrothermal (BAH) process. This BAH process provides an easy and mild way to prepare LP-MSNs with tunable porous structure and mesopore size. Such BAH process enables the transformation from conventionally prepared MSNs with small mesopores (∼2.3 nm) into LP-MSNs with ultra-large mesopore size over 15 nm. This BAH process also enables reliable control over particle sizes (98 nm–278 nm) by varying synthesis conditions. The effect of different synthesis conditions on mesopore enlargement was investigated, including the amounts of initial ethanol, boric acid, and ethanol in mixtures during hydrothermal treatment (HT) and HT temperatures. It is newly found that the ethanol added in synthesis step (1st ethanol), boric acid and ethanol added in mixture during HT process (2nd ethanol) and HT conditions play synergistic roles in the preparation of LP-MSNs with variable mesopore sizes and particle sizes. The underlying principle of such mesopore enlargement by such experimental setup was also analyzed. The BET surface area, pore size, and total pore volume of typical LP-MSNs reach 238 m 2 /g, 15.3 nm, and 0.67 cm 3 /g, respectively. Such LP-MSNs can find different applications in various fields.